2014
DOI: 10.1155/2014/715279
|View full text |Cite
|
Sign up to set email alerts
|

Level of CD8 T Lymphocytes Activation in HIV-Infected Pregnant Women: In the Context of CD38 and HLA-DR Activation Markers

Abstract: Background. To date the effect of pregnancy on the immune activation of CD8 T cells that may affect HIV disease progression has not been well studied and remains unclear. Objective. To determine the effect of pregnancy on CD8 T lymphocyte activation and its relationship with CD4 count in HIV infected pregnant women. Study Design. Case control. Study Site. AMPATH and MTRH in Eldoret, Kenya. Study Subjects. Newly diagnosed asymptomatic HIV positive pregnant and nonpregnant women with no prior receipt of antiretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…High levels of human virus-specific CD38+ CD4+ T cells have been reported to be transiently present during acute presentations also of other infections such as: CMV or EBV infections [ 1 , 46 ]. However, most studies of the role of CD38 antigen on CD4+ cells in antiviral response have focused on HIV infection [ 47 , 48 , 49 ]. Our observation of the decline of CD38+ CD4+ cell population in COVID-19(+) patients relative to other infections was shown here for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of human virus-specific CD38+ CD4+ T cells have been reported to be transiently present during acute presentations also of other infections such as: CMV or EBV infections [ 1 , 46 ]. However, most studies of the role of CD38 antigen on CD4+ cells in antiviral response have focused on HIV infection [ 47 , 48 , 49 ]. Our observation of the decline of CD38+ CD4+ cell population in COVID-19(+) patients relative to other infections was shown here for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Since studies frequently measure HLA-DR co-expressed with CD38 as a marker of activated cells [66][67][68][69], we compared the frequency of CD38+HLA-DR+ NK cells between patient groups. Similar to HLA-DR+ cells, the co-expression of CD38 and HLA-DR was slightly higher in VC-compared to VC+ (Mann-Whitney, p = 0.07, Fig 2C).…”
Section: Plos Onementioning
confidence: 99%
“…The previous study shown that the total CD8 + lymphocytes may not be altered by pregnancy, but activated CD8 + T lymphocyte counts in HIV-positive pregnant women (CD38 + /CD8 + T and HLA-DR + /CD8 + T lymphocytes) were found to be lower than in HIV-positive women who were not pregnant, and the counts were also reduced in the second and third trimesters [ 111 ]. Based on this study, it can be inferred that pregnancy has a significant inhibitory effect on CD8 + T lymphocytes immune activation during HIV infection.…”
Section: The Cd38 Moleculementioning
confidence: 99%
“…Soluble CD38-regulated dendritic cells produce IL-10 and TGF-β, thereby decreasing the cellular immune activity of CD4 + lymphocytes [ 139 ]. Based on these findings about the CD38 molecule, most investigators believe that sustained immune activation of CD8 + T cells may be a marker of progression of HIV infection [ 111 ]. Many investigators have suggested that CD38 on CD8 + T cells alone predicts HIV infection progression independent of viral load and CD4 + T cell count, but others have suggested that the marker itself is not sufficiently sensitive or specific [ 140 ].…”
Section: Future Perspectivesmentioning
confidence: 99%